Celastrol attenuates hepatitis C virus translation and inflammatory response in mice by suppressing heat shock protein 90β - Chen Shao-ru; Li Zheng-qing; Xu Jun; Ding Mo-yu; Shan Ya-ming; Cheng Yung-chi; Zhang Gao-xiao; Sun Ye-wei; Wang Yu-qiang; Wang Ying (Acta Pharmacologica Sinica; Vol 44, No 8 (August 2023): Acta Pharmacologica Sinica, 2023)
Hepatitis C virus (HCV) infection is one of the major factors to trigger a sustained hepatic inflammatory response and hence hepatocellular carcinoma (HCC), but direct-acting-antiviral (DAAs) was not efficient to suppress HCC development. Heat shock protein 90 kDa (HSP90) is highly abundant in different types of cancers, and especially controls protein translation, endoplasmic reticulum stress, and viral replication. In this study we investigated the correlation between the expression levels of HSP90 isoforms and inflammatory response marker NLRP3 in different types of HCC patients as well as the effect of a natural product celastrol in suppression of HCV translation and associated inflammatory response in vivo. We identified that the expression level of HSP90β isoform was correlated with that of NLRP3 in the liver tissues of HCV positive HCC patients (R2 = 0.3867, P